APROXIMACIÓN A LA DEFINICIÓN DE CANAL INFANTIL POLITEMÁTICO DE TELEVISIÓN1 - Irene MELGAREJO MORENO,María del Mar RODRÍGUEZ ROSELL (Fonseca, Journal of Communication, 2023)
The digitalization has created a new way to understand the television channels. There are several authors that have studied this theme –Cebrián (2004), Alcolea (2003), Bustamante (1999), etc. -, however, the approaches that have been made about thematic children’s channels are quite superfluous. This article carries out a revision of the existing theories about television, chilhood and thematic channels that provides a new terminology and formulates an approach to the Polithematic Children´s Channel definition, which shows the XXI Century television reality.